ANALYSIS OF MARKETING STRATEGIES ON MEDICAL TOURISM PROGRAMS IN DEVELOPING COUNTRIES HOSPITALS IN ASIA - Dewi, Ni Putu Indra; Ayuningtyas, Dumilah (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Recently medical tourism is a new form of niche tourism market, which has grown rapidly. The term of Medical Tourism describes tourists who travel to foreign countries to obtain health services and facilities such as medical, dental, surgical care, and so forth. It is necessary to hold a marketing strategy that is able to increase tourist interest in carrying out medical tourism activities in efforts to develop medical tourism. Therefore, the aim of this study was to analyze marketing strategies for medical tourism programs in hospitals. Methods: A systematic review through marketing strategy journals of medical tourism was conducted. Research articles accessed from the internet through databases namely: EBSCO, Emerald, Science direct, Neliti, and Research gate with the keywords medical tourism and medical tourism marketing strategy. The literature analysis from 2 journals with mix methods design, a journal with descriptive qualitative design, a journal with descriptive study design, a journal with SWOT analysis design, a journal with desk research methods design, and 2 journals with data analysis design. Results: The 11 articles that are considered to be in accordance with the objectives of the study. From 11 articles, then screening again based on feasibility according to inclusion and exclusion criteria obtained 8 articles for further review. This systematic review shows that the marketing concepts of segmentation, targeting, and positioning could compete competitively with other hospitals. The marketing strategy of a health service was able to increase the interest of tourists in conducting medical tourism activities in a country. Marketing efforts carried out by hospitals focus on domestic and foreign tourists. Conclusion: The existence of a marketing strategy can increase competitiveness between hospitals and increase the interest of domestic and foreign tourists to carry out medical tourism activities competitively.